1-(3, 5-Dinitro-1H-pyrazol-4-yl)-3-nitro-1H-1, 2, 4-triazol-5-amine (HCPT) and its energetic salts: highly thermally stable energetic materials with high-performance. Issue 44 (26th October 2016) - Li, Chuan; Zhang, Man; Chen, Qishan; Li, Yingying; Gao, Huiqi; Fu, Wei; Zhou, Zhiming
Abstract : A new C–N linked heterocoupled energetic compound and its energetic salts have been prepared as heat-resistant energetic materials. Abstract : A novel energetic heat-resistant explosive, 1-(3, 5-dinitro-1 H -pyrazol-4-yl)-3-nitro-1 H -1, 2, 4-triazol-5-amine (HCPT), has been synthesized along with its salts. An intensive characterization of the compounds is given, including 1 H and 13 C NMR spectroscopy, IR spectroscopy, and elemental analysis. The crystal structures of neutral HCPT (3 ), its triaminoguanidinium salt (10 ), 3, 4, 5-triamino-1, 2, 4-triazolium salt (12 ), and copper(ii ) complex (16 ) were determined by single-crystal X-ray diffraction. The physicochemical properties of the compounds, such as density, thermal stability, and sensitivity towards impact and friction were evaluated; all energetic compounds exhibited excellent thermal stabilities with decomposition temperatures ranging from 215 °C to 340 °C, and high positive heats of formation between 622.8 kJ mol −1 and 1211.7 kJ mol −1 . The detonation pressures and velocities for the energetic compounds were calculated using EXPLO5 (V6.01) based on experimental densities and calculated heats of formation, and the corresponding values were in the ranges of 26.5 GPa to 37.8 GPa and 8236 m s −1 to 9167 m s −1 . Based on thermal stability values and energetic parameters, compounds3 and7 were superior to those of all of the commonly used heat-resistant explosives, which may find potential application as heat-resistant energetic materials.